Dénoncer la violence. Silences et prise de parole autour du harcèlement sexuel envers les travailleuses domestiques au Brésil - Valeria Ribeiro Corossacz (Archivio Antropologico Mediterraneo)
In this paper I present findings of a research carried out in Brazil with domestic workers and union activists concerning the problem of sexual harassment against domestic workers by the male employers. Findings demonstrate how difficult it is to address this problem, for different reasons, in academic literature, in the relationship between domestic workers and union activists, and in the interviews. Domestic workers silence is a way to react to the multiple forms of violence experienced in sexual harassment, a strategic response based on their life conditions. The text discusses in fact how the imbrication of racism, sexism and class inequalities is a key element to understand this sexual harassment, as well women’s responses to it.